MENINGKATKAN KEMAMPUAN SISWA MEMAHAMI DAN MENCIPTA CERITA MATA PELAJARAN BAHASA INDONESIA DENGAN MODEL PROJECT-BASED LEARNING DI KELAS VII-E SMP NEGERI 1 DRIYOREJO KABUPATEN GRESIK SEMESTER GANJIL TAHUN PELAJARAN 2018/2019 - Sri, Sulianing (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Project-based learning is one of active learning by involving students independently with the criteria that in the learning will also increase students' thinking power towards metacognitive things such as thinking critically about projects that will be done through problems found by students. This project-based learning is authentic, so indirectly this learning will involve the learner in constructive investigation. The hope is that through learning that is autonomous, responsibility for students can be better and can bring creative ideas from students because in the execution of the project they will certainly be different in the process than the traditional project or conventional learning this makes the project a meaningful and challenging task . This study aims: 1) Describe teacher activities in improving students' ability to understand and create Indonesian language subject stories with a project-based learning model in Class VII-E Driyorejo State Junior High School 1 Gresik Regency odd semester 2018/2019 Academic Year. 2) Describe the activities of students in learning activities Improve the ability of students to understand and create Indonesian language subject stories with a project-based learning model in Class VII-E Driyorejo 1 Junior High School 1 Gresik Regency odd semester 2018/2019 Academic Year. 3) Describe learning with a project-based learning model in improving students' ability to understand and create stories of Indonesian subjects in Class VII-E Driyorejo 1 Middle School in Gresik Regency. This research is a classroom action research conducted collaboratively. Designing problem situations, and ways to collaborate with children, is the main focus of meetings that occur between teachers and researchers. This research was conducted at Driyorejo State Junior High School 1 Gresik Regency with the address Jl. Raya Tenaru, Dusun Wates, Cangkir, Kec. Driyorejo, Kabupaten Gresik. The subjects of this study were Class VII-E students as many as 32 children. The study was conducted in the odd semester of the 2018/2019 academic year, for 3 months (August, September and October 2018). Procedures for cyclical action research are: 1) planning, 2) implementation, 3) observation, and 4) reflection, through a series of cycles. Data collection through observation (observing), artifacts and documents (testing) and nonstandard tests. Test instrument items with validity test, reliability test, calibration test (level of difficulty) and distinguishing test. the entire process of data analysis is interactive using the Miles and Huberman models with the final mix method analysis. The results of the study concluded: 1) The teacher's activity experienced an increase in Pre-Action obtaining 62.86 percent and increasing in Cycle I by 75 percent and increasing in Cycle II by 87.86 percent; 2) Student activity has increased in Pre-Action to get 42.86 percent and increase in Cycle I by 65 percent and increase in Cycle II by 86.43 percent; 3) The average value of the test (Classical Absorption) has increased in Pre-Action to get a result of 69.68 percent and increase in Cycle I of 73.12 percent and increase in Cycle II of 85.31 percent. Classical Learning Completion has increased in Pre-action obtained 62.5 percent and increased in Cycle I by 84.38 percent and increased in Cycle II by 90.63 percent.